2020
DOI: 10.1007/s10896-020-00217-6
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on the Delivery of an Evidence-Based Child Maltreatment Prevention Program: Understanding the Perspectives of SafeCare® Providers

Abstract: Child maltreatment (CM) is a global public health problem. Evidence-based home visiting programs, such as SafeCare®, reduce CM risk, and enhance parent-child relationships and other protective factors. As the result of the COVID-19 pandemic and resulting restrictions, SafeCare Providers transitioned from home to virtual delivery for the SafeCare curriculum. The purpose of this study is to 1) examine active SafeCare Providers' opinions on the feasibility and effectiveness of SafeCare via remote delivery, and 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 43 publications
5
40
0
1
Order By: Relevance
“…Families adhered to and were highly satisfied with the telehealth counseling sessions, the wireless scale and weight graph to track child weight, and the pedometer to track child physical activity. These findings are consistent with emerging research documenting that families are responding well to SafeCare delivery via technology, a delivery approach that was implemented as a result of the COVID-19 pandemic [ 8 ]. Integrating the intervention into a comprehensive smartphone app or website may enable a more seamless delivery system of both self-monitoring tools and ongoing remote interaction with the counselor.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Families adhered to and were highly satisfied with the telehealth counseling sessions, the wireless scale and weight graph to track child weight, and the pedometer to track child physical activity. These findings are consistent with emerging research documenting that families are responding well to SafeCare delivery via technology, a delivery approach that was implemented as a result of the COVID-19 pandemic [ 8 ]. Integrating the intervention into a comprehensive smartphone app or website may enable a more seamless delivery system of both self-monitoring tools and ongoing remote interaction with the counselor.…”
Section: Discussionsupporting
confidence: 87%
“…However, the family must have the necessary equipment including an internet-enabled device (eg, smartphone, tablet, or computer that is connected to the internet via either a cellular network or WiFi). A recent study of the virtual delivery of SafeCare indicated that many families experienced limited broadband access and technology fatigue, resulting in the need to deliver shorter counseling sessions less than 30 minutes in length [ 8 ]. Online interactions may also lessen rapport between the provider and family due to limited ability to see nonverbal cues such as body language.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some digital interventions have been developed and implemented (Honda et al, 2020 ), social services workers have expressed mixed opinions about family engagement and improvement levels (Self-Brown et al, 2020 ). It has been argued that face-to-face meetings are irreplaceable (Jentsch & Schnock, 2020 ).…”
Section: The Shutdown Of Formal Systemsmentioning
confidence: 99%
“…Additionally, child protection services face various challenges in adapting CM prevention to the COVID-19 reality. A recent study examined the implementation of the Safe-Care preventive initiative during the pandemic in an online platform (Self-Brown et al, 2020 ). Along with recognizing the success of this attempt, the researchers indicated that this solution was only relevant to families with access to computers and the internet, which is not the reality for many children and their families across the globe.…”
Section: The Shutdown Of Formal Systemsmentioning
confidence: 99%